Comparative Analysis of Field Oriented Control and Direct Torque Control Through Simulation in MATLAB Simulink for an Automotive Drive Motor - Miklós Gábor Simon; Dénes Fodor (Engineering Proceedings)
Field oriented control (FOC) and direct torque control (DTC) are two strategies used in electric motor control, both with their respective advantages and disadvantages. This paper presents a comparative analysis of these two control methodologies, focusing on their application and performance within a MATLAB Simulink (R2024b) environment for an automotive Permanent Magnet Synchronous Motor (PMSM) drive. The models are created with a focus on realistic drive and test parameters. The simulation results are analyzed to highlight the strengths and weaknesses of each strategy and identify use cases where one method may be superior to the other. In conclusion, this paper contributes to the understanding of FOC and DTC by offering a systematic comparison of their features, performance characteristics, and application scenarios for automotive use.